Hubungan Kualitas Pelayanan Informasi Obat Terhadap Kepuasan Pasien Puskesmas II Denpasar Timur Di Era New Normal - Artawan, I Putu Hendra Juli; Widowati, I Gusti Ayu Rai; Aman, IGM (Bali International University, 2023)
Background: Drug information service is an activity carried out by pharmacists in providing information about drugs that is impartial, critically evaluated and with the best evidence in all aspects of drug use in other health professionals, patients or the public. While drug information is an activity to provide information, drug recommendations that are independent, accurate, comprehensive, up-to-date, by pharmacists to patients. The provision of drug information has an important role in improving the quality of life of patients and providing quality services for patients. Objective : This study was to determine the relationship between drug information service quality and patient satisfaction at Puskesmas II, East Denpasar. Methods: The study was conducted in an analytical observational manner with a cross sectional design. Sampling was carried out with Non Probability Sampling, which is consecutive, which was then analyzed using univariate analysis and bivariate analysis. Results: Based on the analysis seen from the sig (2-tailed) and Correlation coefficient, it is known that there is a relationship between the quality of drug information services and patient satisfaction at PIO at Puskesmas II East Denpasar, with a significance value of 0.05 and a correlation coefficient of 0.524 with strong relationship category. Conclusion: The quality of Drug Information Services at Puskesmas II East Denpasar is reported to be good. Between the quality of Drug Information Services and patient satisfaction at Puskesmas II East Denpasar.